On the structure of cetylpyridinium perchlorate: A combined XRD, NMR, IR and DFT study - Oksana Fizer; Фізер Оксана; Maksym Fizer; Фізер Максим; Filep Mykhailo; Філеп Михайло; Filep Mihály; Sidey Vasyl; Сідей Василь; Ruslan Mariychuk; Марійчук Руслан (My University, 2022)
Abstract. Cetylpyridinium perchlorate has been synthesized and characterized by using the differential thermal analysis (DTA), X-ray powder diffraction (XRD) techniques, Fourier transform infrared spectroscopy (FT-IR), and 1H and 13C nuclear magnetic resonance (NMR) spectroscopy. The investigated salt melts congruently at 100 °C. The DTA and XRD results indicate that the cetylpyridinium perchlorate samples synthesized at different temperatures differ in crystallinity. It has been established that the crystallinity degree of the samples affects the decomposition temperature. The highest decomposition temperature (Td = 265 °C) is observed for the sample crystallized at 20 °C. Cetylpyridinium perchlorate crystallizes in the monoclinic crystal system with the cell parameters a = 20.31 Å, b = 16.20 Å, c = 7.25 Å, β = 95.26°, Z = 4. According to the DFT calculations, the interionic interactions in the structure are characterized by electron transfer from the perchlorate anion to the cetylpyridinium cation. This explains a noticeable difference in the 1H NMR chemical shifts of the hydrogen atoms in the ortho-position (∼0.2 ppm) and the α-methylene group (∼0.1 ppm) of the DMSO solutions of the cetylpyridinium perchlorate and chloride salts micelles. The electronic structure analysis of cetylpyridinium perchlorate and cetylpyridinium chloride in terms of the “quantum theory of atoms-in-molecules” and the analysis of non-covalent interactions with the “reduced density gradient” method have revealed the presence of strong interactions between the ions in the DMSO solution.
Contents: https://www.sciencedirect.com/journal/journal-of-molecular-liquids/vol/368/part/PA
Keywords: cetylpyridinium; charge transfer; conductometry; micelle; perchlorate; XRD